Zakat Community Development Program Through A Zakat Village Index Approach - Susilawati, Nilda; Sunarto, Andang; Rohimin, Rohimin (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2019)
This research is motivated by the level of poverty that exists in the District of Sukaraja, Seluma Regency. It is necessary to have a community empowerment program through the zakat community development program. The zakat community development program is a form of community empowerment program in certain villages to enliven or develop the potential of the community through creative industries that produce superior products. Thus, the community is able to be economically independent. The method used is a field research with a descriptive qualitative mixed approach with quantitative using the Zakat Village Index (Indek Desa Zakat/ IDZ). The data consists of primary and secondary data and data collection techniques through observation, questionnaires and interviews with sources and research informants from competent parties. From the results of the study, it was found that in Sukaraja District, there was one village prioritized to be assisted with an IDZ score in the range 0.21-0.40, 13 villages could be considered to be assisted with an IDZ score in the range 0.41-0.60 and 7 villages were less prioritized to be assisted with IDZ scores in the range of 0.61-0.80 through the zakat program. With the zakat community development program in the form of home industry business development programs, animal husbandry and agricultural or plantation businesses. Penelitian ini dilatarbelakangi oleh tingkat kemiskinan yang terjadi di Kecamatan Sukaraja Kabupaten Seluma, maka perlu program pemberdayaan masyarakat melalui program zakat community development. Program zakat community development ini merupakan salah satu bentuk program pemberdayaan sekelompok masyarakat pada desa tertentu untuk menghidupkan atau mengembangkan potensi yang dimiliki masyarakat melalui industri kreatif yang menghasilkan produk unggulan. Sehingga masyarakat mampu mandiri secara ekonomi. Metode yang digunakan adalah field reseach dengan pendekatan mixed kualitatif deskriptif dengan kuantitatif menggunakan Indeks Desa Zakat (IDZ). Data terdiri dari data primer dan sekunder dan teknik pengumpulan data melalui observasi, angket dan wawancara dengan sumber dan informan penelitian berasal dari pihak yang berkompeten. Dari hasil penelitian ditemukan bahwa di Kecamatan Sukaraja terdapat 1 desa diprioritaskan untuk dibantu dengan score IDZ berada pada range 0,21-0,40, 13 desa dapat dipertimbangkan untuk dibantu dengan score IDZ pada range 0,41-0,60 dan 7 desa kurang diprioritaskan untuk dibantu dengan score IDZ pada range 0,61-0,80 melalui program zakat. Dengan program zakat community development berupa program pengembangan usaha home industri, peternakan dan usaha pertanian atau perkebunan.